HISTORICAL-GEOGRAPHICAL ANALYSIS OF SETTLEMENT PATTERN FORMATION IN RA FRONTIER, MOUNTAINOUS AND HIGH MOUNTAINOUS AREAS (Proceedings of the YSU C: Geological and Geographical Sciences, 2019)
The current tendencies of development and changes taking place in the settlement system of RA frontier, mountainous and high mountainous territories are largely dependent on historical-geographical features of those areas among other factors. Historical-geographical analysis of settlement pattern basis formation of RA frontier, mountainous and high mountainous areas have been done in the article.
Keywords: frontier areas; mountainous areas; settlement pattern; historicalgeographical analysis